Cognitive‐Behavioral Couple Therapies: Review of the Evidence for the Treatment of Relationship Distress, Psychopathology, and Chronic Health Conditions. Issue 3 (26th May 2016) - Fischer, Melanie S.; Baucom, Donald H.; Cohen, Matthew J.
Abstract : Cognitive‐behavioral couple therapy (CBCT) is an approach to assisting couples that has strong empirical support for alleviating relationship distress. This paper provides a review of the empirical status of CBCT along with behavioral couple therapy (BCT), as well as the evidence for recent applications of CBCT principles to couple‐based interventions for individual psychopathology and medical conditions. Several meta‐analyses and major reviews have confirmed the efficacy of BCT and CBCT across trials in the United States, Europe, and Australia, and there is little evidence to support differential effectiveness of various forms of couple therapy derived from behavioral principles. A much smaller number of effectiveness studies have shown that successful implementation in community settings is possible, although effect sizes tend to be somewhat lower than those evidenced in randomized controlled trials. Adapted for individual problems, cognitive‐behavioral couple‐based interventions appear to be at least as effective as individual cognitive behavioral therapy (CBT) across a variety of psychological disorders, and often more effective, especially when partners are substantially involved in treatment. In addition, couple‐based interventions tend to have the unique added benefit of improving relationship functioning. Findings on couple‐based interventions for medical conditions are more varied and more complex to interpret given the greater range of target outcomes (psychological, relational, and medical variables). Abstract : Translation into Spanish